The role of febuxostat in gout. Issue 2 (March 2019) - Bardin, Thomas; Richette, Pascal
Abstract : Purpose of review: Concerns about the cardiovascular safety of febuxostat lead to reconsideration of the place of febuxostat in the management of gout. Recent findings: The CARES trial is a randomized controlled trial mandated by the FDA to compare the cardiovascular safety of febuxostat and allopurinol in the management of gout. About 6190 patients with gout and major cardiovascular disease, randomly assigned to allopurinol or febuxostat, were prospectively followed up for a median of 32 months. No difference was noted in the occurrence of the primary end-point event, a composite of cardiovascular death, nonfatal myocardial infarction, nonfatal stroke, or unstable angina with urgent revascularization, but cardiovascular death was significantly more common in the febuxostat group (4.3%) as compared with the allopurinol group (3.2%) ( P  = 0.03). Summary: Present guidelines on the management of gout should be revised in view of recent findings. Allopurinol could be recommended as the sole first-line urate-lowering drug (ULD) in patients with no contraindication. In patients contraindicated to allopurinol, uricosurics could be preferred to febuxostat as first-line ULDs in patients with cardiovascular disease/risk factors and no history of uric acid stones.